Discourse Coherence in Pronoun Resolution - Clare Patterson (Discours, 2013)
According to “Centering Theory”, an entity that links to the prior discourse could receive a boost in the current prominence ranking. Such a boost will affect pronoun processing because pronouns tend to seek out the most prominent entity for reference. The current paper presents a reanalysis of data from a study that investigated how pronoun processing was affected by the prior discourse. In an eye-movement monitoring experiment, English speakers were presented with texts that manipulated (1) the pronoun’s gender match with possible antecedents and (2) the appearance of the antecedents in prior discourse. The results showed that prior discourse affected eye-movement measures from the pronoun region onwards, but the antecedents were differently affected by this manipulation. The results can be accounted for if the overall discourse coherence is taken into account, especially the number of switches in attention that a reader/hearer has to make. More attention switches in a relatively short discourse may have created uncertainty about the local discourse topic, making pronoun processing more problematic. This study shows that the prior discourse can influence the processing of pronouns, but processing is also affected by coherence.